[Anemia as a prognostic factor in cancer patients] - Paitan, V (2018)
Objective.: To determine the frequency and prognostic value of anemia in cancer patients receiving care at the National Institute of Neoplastic Diseases (Instituto Nacional de Enfermedades Neoplásicas - INEN) between January and April of 2010. Materials and methods.: Anemia was considered for men with hemoglobin levels at <13 g/dL; and for women, at <12 g/dL. Associations between qualitative features were assessed with a Chi-square test. Kaplan-Meier estimator was used for the analysis of the survival curves, and differences between the curves were performed with the log-rank test. Results.: 772 patients were included; 584 (75.7%) had solid tumors and 188 (24.3%) had hematologic malignancies. Anemia was diagnosed in 359 patients (46.5%); hematologic malignancies in 127 patients (67.6%); and solid neoplasms in 235 (40.2%). Hematologic malignancies with the highest frequency of anemia were chronic myeloid leukemia, acute leukemias, and multiple myeloma (100%, 92.5% and 60%, respectively); and were cancer of gastrointestinal, gynecological, and urological origin were in the group of solid neoplasms (62%, 52.1% and 45%, respectively). Two hundred and four (204) patients (26.4%) were transfused. In 762 patients, a significant difference in overall survival was found between groups with and without anemia, estimated at 5 years in 62% and 47% respectively (p <0.001). In the solid tumor subgroup (p = 0.002), and the hematological malignancies subgroup (p = 0.007), such association was also found. Conclusions.: Anemia is common in cancer patients, and its presence determines an independent prognostic factor in overall survival.